Papel de MIF (Fator de Inibição de Migração de Macrófagos) na proteção de células trofoblásticas (BeWo) e explantes de terceiro trimestre contra infecção por Toxoplasma gondii - Gomes, Angelica de Oliveira (2008)
Macrophage Migration Inhibitory Factor (MIF) performs various roles. It s immunological functions include the modulation of the host response to pathogens. In contrast to other known cytokines, MIF production is induced rather than suppressed by glucocorticoids, and MIF has been found to override the immunosuppressive effects of glucocorticoids. The aim of this study was to verify the role of MIF on the defense of trophoblastic cells (BeWo) like a experimental model of first trimester of pregnancy and placental explants of third trimester against infection by Toxoplasma gondii. For this purpose, BeWo cells were incubated in culture medium treated or not with STAg, rMIF, anti-MIF, supernatants of cultured cells (SPN) pre stimulated for MIF production, or SPN plus anti-MIF. Followed by infection or sham-infection with T. gondii the cells were again incubated in the presence of the same stimulus. Supernatants of BeWo cells were assessed for MIF production. BeWo cells were processed to measure replication of parasites and index of infection and for immunocitochemistry assay. In addition, placental explants were stimulated or not with STAg and infected or not with T. gondii. Explants were processed for morphologic and immunohistochesmistry analyses and supernatants were accessed for MIF production. Results showed that MIF is increased in supernatants of cultured BeWo cells infected with T. gondii or stimulated with STAg compared with non infected cells. However, it wasn´t observed for placental explants. The index of infection and replication of parasites increased with blockade of endogenous MIF and reduced in presence of exogenous MIF in BeWo cells. Thus, we conclude that MIF is an important factor in control of T. gondii infection in BeWo trophoblastics cells. The lack up regulation of MIF by infection in third trimester placental explants may have relationship with the more susceptible to infection at this gestational age.